New venture investing trajectories: A large scale longitudinal study - Reinhard Schulte (Leuphana Universität Lüneburg, Lehrstuhl Gründungsmanagement, 2018)
Investment trajectories of new enterprises are a largely neglected but important issue of new firms' business behavior. This paper debuts in showing robust evidence of new venture investment time patterns by using investment time series of 4.733 new businesses. Based on a fixed effects nonlinear panel regression approach, the study models the trajectory of new venture asset acquisition in the first years after market entry. The results unveil durations and levels of investment patterns. Showing a first investment peak at market entry and a second peak years later, an initial new venture investment cycle is bimodal. Its peak-to-peak duration yields approximately nine years on average. New venture investment can be staggered into three stages, namely an initial, a plateau, and a replacement and expansion stage.
urn:nbn:de:101:1-2019121610393249310747
Keywords: D92; G31; L25; M13; M21; 330; new ventures; start-up; investment pattern; investment trajectory; fixed effects model; panel data